STRATEGIC DIRECTIONS FOR THE SOCIO-ECONOMIC DEVELOPMENT OF THE DISTRICTS OF THE KHOREZM REGION FOR 2025–2030 BASED ON CLUSTERING - Ruziboyeva , Mushtariy Otabek qizi (THE INNOVATION ECONOMY, 2026)
This article analyzes the strategic directions of socio-economic development of the districts of the Khorezm region for 2025–2030 based on their clustering. Considering the level of economic specialization, resource potential, and infrastructure development, a differentiated development model has been developed by dividing the territories into four clusters.